Communicative implication in Qur'anic address based on Grace's theory "Case Study: The Story of Zakaria and Maryam (peace be upon them)" - Kaveh Rahimi; Sudabeh Mozaffari; Ali Asvadi (دراسات في اللغة العربيّة وآدابها)
Undoubtedly, communicative implication is one of the most prominent concepts in new applied modern linguistic research in the West. The communicative implication has highlighted the miraculous aspects of the Holy Qur'an, and its importance is manifested in the interpretation of the Qur'anic compositions and its relation to the present. It seems necessary to make a comparative analysis of the theory of communicative implication in the light of the story of Zakaria and Maryam (peace be upon them) in Surahs of Al-e-Imran and Maryam, and the reason for choosing these two stories is that they are based on the most expressive and fascinating Qur'anic stories in extraordinary adventures. Their approach, style and educational teachings have a great impact on the behavior of the audience, the absorption of ideas and guidance of human beings. Since moral-educational teachings in the form of stories always affect the audience more than other writings, as a result, God - the Exalted - has placed the story as persuasion and influence in the Qur'an and at the same time, he has presented his reasons and arguments to the deniers and polytheists. Based on the principle of Grace's cooperation, the present study has achieved the following results: Ten conversations in the two mentioned stories have deviated from real meanings to secondary meanings in accordance with one of Grace's four principles and using demonstratives, semantics and expressions; Until the dignity, the answer to the prayer of Zakaria (AS) and the gift of a child to him in old age, despite the infertility of his wife, the miraculous birth of Jesus (AS) and the innocence of Mary (AS) from the ugly words attributed to her by her people to be revealed. Deviation from the principle of quantity and quality is one of the most frequent types of communicative implication in the dialogues of two stories.